1997
DOI: 10.1002/pro.5560060112
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant hirustasin: Production in yeast, crystallization, and interaction with serine proteases

Abstract: A synthetic gene coding for the 55-amino acid protein hirustasin, a novel tissue kallikrein inhibitor from the leech Hirudo medicinalis, was generated by polymerase chain reaction using overlapping oligonucleotides, fused to the yeast a-factor leader sequence and expressed in Saccharomyces cerevisiae. Recombinant hirustasin was secreted mainly as incompletely processed fusion protein, but could be processed in vitro using a soluble variant of the yeast yscF protease. The processed hirustasin was purified to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…This sequence is consistent with the intracellular processing of residues 1-64 of the ␣-factor leader peptide, resulting from the cleavage of the bond between Leu64 and Phe65. Interestingly, the N-terminal sequence found in the secreted precursor was the same as the one reported for a secreted ␣-factor-hirustatin fusion containing a wild-type ␣-factor leader sequence (29). Although the N-terminal extension does not affect the activity of hirustatin (29), its presence appears to abolish the inhibitory activity of the secreted ␣-factor-hirudin fusion protein.…”
Section: Expression Of An Inactive Hirudin Fusion and Its Activation supporting
confidence: 58%
“…This sequence is consistent with the intracellular processing of residues 1-64 of the ␣-factor leader peptide, resulting from the cleavage of the bond between Leu64 and Phe65. Interestingly, the N-terminal sequence found in the secreted precursor was the same as the one reported for a secreted ␣-factor-hirustatin fusion containing a wild-type ␣-factor leader sequence (29). Although the N-terminal extension does not affect the activity of hirustatin (29), its presence appears to abolish the inhibitory activity of the secreted ␣-factor-hirudin fusion protein.…”
Section: Expression Of An Inactive Hirudin Fusion and Its Activation supporting
confidence: 58%
“…Primary structural and X-ray crystallographic studies of antistasin and hirustasin have suggested that antistasin-type inhibitors have a similar disulfide bond pattern or tertiary structure (4,32,33). However, guamerin has a unique inhibition property toward elastase that is distinct from other antistasin-type inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the reactive-site loop was partially demonstrated by the inhibitory activity of a disulRecently, X-ray crystallography of the hirustasin · tissue kallikrein complex [18,19] and the antistasin · factor Xa complex fide-bridge formation consisting of 19-residue peptides that contained the reactive-site sequence of guamerin [22]. Piguamerin [20,21] revealed the molecular interactions of the inhibitors with target proteases.…”
mentioning
confidence: 99%